Optimizing Lifting Equipment Safety in Container Handling Operations: A Comprehensive Strategy to Minimize Workplace Accidents at PT Pelindo Terminal Petikemas New Makassar - AGUS SULISTIONO (PIP Makassar, 2026)
Workplace accidents at ports, particularly during the operation of container handling equipment, remain a critical issue that threatens both worker safety and operational efficiency. At the New Makassar Container Terminal, despite the implementation of safety procedures, gaps in their execution persist, increasing the risk of accidents. This study aims to identify the factors affecting workplace safety in the operation of lifting equipment at the New Makassar Container Terminal and to formulate strategies for optimizing workplace safety. Using a mixed-methods approach, the research combines qualitative methods (case study, in-depth interviews, field observations, and document analysis) with quantitative methods (statistical analysis of accident data). The findings indicate that technical factors, such as equipment condition and maintenance, human factors related to training and safety communication, and environmental factors like extreme weather, significantly contribute to workplace accidents. This research recommends enhancing preventive equipment maintenance, improving the socialization of Standard Operating Procedures (SOPs), and implementing digital technology for real-time monitoring of equipment and weather conditions to improve workplace safety at the port. These findings are applicable not only to large ports in Indonesia but also globally.